Hard carbon negative electrode material, preparation method thereof and battery
By fixing nanoscandium oxide in hard carbon matrix materials to form a mosaic conductive network structure, the problem of insufficient compaction density and electrochemical performance of hard carbon materials in sodium ion batteries is solved, and efficient sodium ion battery performance improvement and safety improvement are achieved.
Patent Information
- Application Number
- CN202411901954.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The compaction density and electrochemical performance of hard carbon materials in sodium ion batteries are insufficient, resulting in poor first-effect and rate performance of the battery, and there are safety hazards such as short circuit inside the battery, thermal runaway and fire explosion.
By fixing nanoscandium oxide in the pore structure of the hard carbon matrix material, a mosaic conductive network structure is formed, the compaction density and electrochemical properties of the material are improved, and uniform mixing and efficient compaction are achieved through the addition of binder and spray drying technology.
It significantly improves the compaction density and electrochemical performance of hard carbon negative electrode materials, improves the first-effect and rate performance of sodium ion batteries, and reduces safety hazards.
Smart Images

Figure CN119725526A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and relates to a hard carbon negative electrode material and a preparation method thereof, and a battery, and in particular to a hard carbon negative electrode material for a sodium ion battery and a preparation method thereof, and a sodium ion battery. Background Art
[0002] Lithium-ion batteries are widely used in 3C consumer electronics, new energy electric vehicles, and renewable energy storage. Limited lithium resources, unbalanced distribution, and high costs are not conducive to their large-scale application in the field of energy storage. At the same time, the graphite negative electrode of commercial lithium-ion batteries hinders the further improvement of battery cycle performance and rate performance due to its structural characteristics. Sodium-ion batteries have a similar energy storage mechanism to lithium-ion batteries, and are expected to replace lithium-ion battery products due to their advantages such as abundant resources and low cost.
[0003] Hard carbon has randomly oriented graphite domains, a higher carbon layer spacing and some residual heteroatoms (mainly oxygen functional groups). The disordered structural carbon can provide more ion diffusion paths and ion storage sites, especially sodium ion diffusion paths and sodium ion storage sites, and is currently a more preferred negative electrode material for sodium ion batteries.
[0004] Hard carbon materials are usually obtained by high-temperature heat treatment of organic precursors in a protective gas atmosphere. During the high-temperature pyrolysis process, the carbon precursor material decomposes and releases volatile gases. The released gases form pores in the hard carbon material, resulting in a high specific surface area, high porosity and low volume density of the hard carbon material, which brings about problems such as low compaction density, low first-cycle coulomb efficiency and poor cycle performance of the hard carbon material; and the irregular morphology causes the rupture of the current collector under high compaction conditions, leading to safety problems such as internal short circuit, thermal runaway, fire and explosion of the battery.
[0005] Therefore, how to improve the compaction density and electrochemical performance of hard carbon materials is a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a hard carbon negative electrode material and a preparation method and a battery. In the present invention, nano scandium oxide is fixed in the pore structure of the hard carbon matrix material as a support, which improves the compaction density of the hard carbon negative electrode material on the one hand, and forms an embedded conductive network structure on the other hand, thereby improving the electrochemical performance of the hard carbon negative electrode material.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a hard carbon negative electrode material, wherein the hard carbon negative electrode material comprises a hard carbon matrix material, wherein the hard carbon matrix material has a pore structure, and nano scandium oxide is fixed in the pore structure.
[0009] The hard carbon negative electrode material provided by the present invention has nano scandium oxide with high conductivity, which can promote the selective adsorption of ester groups and carbonyl groups of sodium ion electrolyte, thereby inhibiting the occurrence of side reactions between hard carbon and electrolyte, reducing the formation of SEI film, and allowing more sodium ions to participate in the reversible embedding and extraction process, thereby improving the primary effect of hard carbon; nano scandium oxide is also fixed in the pore structure of the hard carbon matrix material as a support to form a mosaic conductive network structure, which can effectively prevent the aggregation and loss of scandium oxide particles, so that the hard carbon particles are evenly distributed, and even at high rate charge and discharge, electrons can be quickly transmitted in the electrode material.
[0010] At the same time, the high specific surface area of nano-scandium oxide enables it to have more contact points with the hard carbon particles, generating van der Waals force. This force helps to pull the hard carbon particles towards each other during the pressing process, making them more tightly combined together, thereby improving the compaction density of the material. Furthermore, nanoparticles have a larger specific surface area and more surface atoms. These surface atoms have higher chemical activity and thus become potential active sites. These active sites will react chemically with the functional groups on the surface of hard carbon (such as carboxyl, hydroxyl, etc.) to form chemical bonds. The chemical bonding effect can enhance the connection strength between the hard carbon particles, making it less likely for the hard carbon particles to undergo relative displacement during the compaction process, thereby being able to withstand higher pressures and achieve higher compaction densities.
[0011] That is, the hard carbon negative electrode material provided by the present invention has high compaction density and excellent electrochemical performance, especially when used in sodium ion batteries, the first efficiency and rate performance of the battery are greatly improved.
[0012] In the present invention, if the scandium oxide is at the micron level, it cannot fill the gaps as effectively as nano-scale scandium oxide due to its larger particle size, resulting in the mechanical properties of the hard carbon material not being as significantly improved as nano-scale scandium oxide.
[0013] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0014] Preferably, the surface of the nano scandium oxide is modified with oxygen bridge bonds.
[0015] It should be noted that the oxygen bridge bond in the present invention is Sc-O-Sc, which is formed by nucleophilic addition between the hard carbon precursor and scandium oxide and then by eliminating water.
[0016] In the present invention, the surface of nano scandium oxide is modified with oxygen bridge bonds, which can better promote the selective adsorption of ester groups and carbonyl groups of sodium ion electrolytes, thereby inhibiting the occurrence of side reactions between hard carbon and electrolytes, reducing the formation of SEI films, and allowing more sodium ions to participate in the reversible embedding and extraction process, thereby further improving the initial efficiency of sodium ion batteries.
[0017] Preferably, the median particle size D50 of the nano scandium oxide is 5 to 250 nm, for example, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm or 250 nm, etc.
[0018] In the present invention, the median particle size D50 of nano scandium oxide is adjusted to 5-250 nm, which is more conducive to the high specific surface area of scandium oxide, thereby providing more active sites for the hard carbon material, thereby further improving the electrochemical performance of the battery.
[0019] Preferably, the hard carbon matrix material comprises a resin-based hard carbon matrix material.
[0020] Resin-based hard carbon matrix materials, that is, hard carbon materials obtained by using resin as raw materials, consume more electrolyte and sodium ions to generate SEI (solid electrolyte interface) film during the first charging process, which leads to a decrease in the first coulomb efficiency; there is contact resistance between hard carbon particles, and no good conductive network is formed during the material preparation process. During high-rate charging and discharging, electrons cannot be quickly transmitted in the electrode material; at the same time, resin-based hard carbon particles usually present irregular shapes, such as block, sheet or complex polyhedral structure. This irregularity makes it difficult for particles to form a tight arrangement when stacked, which results in a lower proportion of solid part in the hard carbon material under the same volume, that is, a lower compaction density.
[0021] The hard carbon matrix material in the present invention is selected from a resin-based hard carbon matrix material, and cooperates with nano scandium oxide, which is more conducive to improving its first effect. Nano scandium oxide can promote selective adsorption of electrolyte, inhibit side reactions, reduce SEI film formation, and improve the first effect. Nano scandium oxide and hard carbon materials form a mosaic conductive network structure to prevent particle aggregation and loss, thereby improving the compaction density of the hard carbon material.
[0022] Preferably, the porosity of the hard carbon matrix material is 20% to 55%, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50% or 55%.
[0023] Preferably, the D50 of the hard carbon negative electrode material is 5 to 10 μm, for example, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 10 μm.
[0024] In a second aspect, the present invention provides a method for preparing the hard carbon negative electrode material as described in the first aspect, the preparation method comprising the following steps:
[0025] The hard carbon negative electrode material is obtained by mixing nano scandium oxide, a hard carbon precursor material and a binder solution, compacting and molding, and carbonizing.
[0026] The preparation method provided by the present invention uniformly mixes the nano scandium oxide and the hard carbon precursor material under the action of a binder, and effectively improves the compaction density of the material through a subsequent compaction molding process. After a subsequent carbonization process, the nano scandium oxide is fixed in the pore structure of the hard carbon matrix material as a support, and has excellent compaction density and electrochemical properties. The preparation method is simple to operate, does not require a complicated processing process, and is suitable for commercial production.
[0027] In the present invention, if a binder is not added, the nano scandium oxide and the hard carbon precursor material cannot form a stable and uniform mixed system during the mixing process; and if compaction molding is not performed, the particles will not be forced to move and fill the gaps between adjacent particles, and there will be gaps between the particles, which is not conducive to improving the compaction density of the material; that is, the addition of the binder and the subsequent compaction molding process work together to achieve a high compaction density of the prepared hard carbon negative electrode material.
[0028] Preferably, the preparation method of the nano scandium oxide comprises:
[0029] The scandium salt solution and the precipitant solution are mixed and dispersed, a co-precipitation reaction is carried out, and sintering is performed to obtain nano scandium oxide.
[0030] It should be noted that the present invention does not specifically limit the specific method of mixing and dispersing, and the present invention is applicable to any method that can achieve uniform mixing of raw materials; for example, ultrasonic dispersion can be performed, and the ultrasonic dispersion time can be 0.5 to 1.5 hours (for example, 0.5 hours, 1 hour or 1.5 hours, etc.).
[0031] Furthermore, the scandium salt includes but is not limited to at least one of scandium sulfate, scandium acetate, scandium chloride or scandium citrate; the precipitant includes but is not limited to at least one of sodium oxalate, sodium carbonate, disodium hydrogen phosphate or sodium dihydrogen phosphate.
[0032] The present invention prepares a nano-scale scandium oxide material, which is more conducive to the composite of the scandium oxide material and a hard carbon precursor material.
[0033] Preferably, the mixing and dispersing process also includes a surfactant solution.
[0034] During the preparation of nano-scandium oxide, in the initial nucleation stage, the size of the crystal nucleus will gradually increase due to the continuous collision and aggregation of the scandium salt precipitates in the system. When the crystal nucleus reaches a certain size, its growth becomes uncontrollable. The addition of surfactants can form an interfacial film on the surface of the solution to prevent the agglomeration of nanoparticles, so that the prepared nanoparticles have better dispersibility, and a nano-scale scandium oxide material with uniform particle size is obtained.
[0035] Preferably, the surfactant comprises any one of glycerol, polyethylene glycol, Span or Tween, or a combination of at least two thereof.
[0036] Preferably, the molar ratio of the scandium salt, the precipitant and the surfactant is 1:(1-5):(0.5-1.5), for example, 1:1:0.5, 1:1:0.8, 1:1:1, 1:1:1.3, 1:1:1.5, 1:2:0.5, 1:2:0.8, 1:2:1, 1:2:1.3, 1:2:1.5, 1:3:0.5, 1:3:0.8, 1:3:1, 1:3:1.3, 1:3:1.5, 1:4:0.5, 1:4:0.8, 1:4:1, 1:4:1.3, 1:4:1.5, 1:5:0.5, 1:5:0.8, 1:5:1, 1:5:1.3 or 1:5:1.5, etc.
[0037] Preferably, the concentration of the scandium salt solution is 0.5-3.5 mol / L, for example, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L or 3 mol / L.
[0038] Preferably, the concentration of the precipitant solution is 1-6 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L or 6 mol / L.
[0039] Preferably, the concentration of the surfactant solution is 0.1-1.5 mol / L, for example, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L or 1.5 mol / L, etc.
[0040] Preferably, the pH value of the coprecipitation reaction is 8-10, for example, 8, 8.3, 8.5, 8.8, 9, 9.3, 9.5, 9.8 or 10.
[0041] In the present invention, the method for adjusting the pH value during the coprecipitation reaction is not limited. The present invention is applicable to any method that can adjust the pH value without affecting the normal progress of the reaction. For example, ammonia water can be added to adjust the pH value in the system.
[0042] Preferably, the reaction solution after the coprecipitation reaction is freeze-dried.
[0043] Preferably, the freeze-drying time is 6 to 36 h, for example, 6 h, 10 h, 12 h, 15 h, 18 h, 20 h, 24 h, 25 h, 27 h, 30 h, 33 h, 35 h or 36 h.
[0044] Preferably, the sintering temperature is 450-850°C, for example, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C or 850°C.
[0045] Preferably, the sintering time is 0.5 to 2 h, such as 0.5 h, 1 h, 1.5 h or 2 h.
[0046] Preferably, the added amount of the nano scandium oxide is 0.5% to 5% of the mass of the hard carbon precursor material, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.
[0047] In the present invention, the added amount of the nano scandium oxide is 0.5% to 5% of the mass of the hard carbon precursor material, which can better achieve good transmission of sodium ions during the charging and discharging process.
[0048] Preferably, the added amount of the binder is 5% to 10% of the mass of the hard carbon precursor material, for example, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%, etc.
[0049] In the present invention, the amount of the binder added is 5% to 10% of the mass of the hard carbon precursor material, which can better improve the porosity of the hard carbon material; if a large amount of binder is added, it will fill the pores of the hard carbon material. After spray drying, the binder will solidify and occupy the space originally belonging to the pores, thereby greatly reducing the porosity of the hard carbon material.
[0050] Preferably, the hard carbon precursor material comprises resin.
[0051] It should be noted that, in addition to resin, the hard carbon precursor material in the present invention may also be selected from biomass carbon sources and coke carbon sources, and is further preferably resin. The specific material type selection of the resin in the present invention is a conventional technical solution. For example, the resin includes at least one of phenolic resin, urea-formaldehyde resin, epoxy resin, melamine resin or lignin phenolic resin.
[0052] Preferably, the binder includes any one of paraffin, polyvinyl alcohol, polymethyl methacrylate or polyurethane, or a combination of at least two thereof.
[0053] Preferably, the concentration of the binder solution is 1-10 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L or 10 mol / L.
[0054] Preferably, the mixed solution is spray-dried and then compacted and molded.
[0055] In the present invention, the nano scandium oxide can be evenly dispersed in the hard carbon precursor material by the spray drying method. In the process of droplet formation and drying, the nano scandium oxide particles can be fully mixed with the hard carbon precursor material. With the rapid evaporation of the solvent, the highly conductive nano scandium oxide is fixed in the pore structure of the hard carbon as a support to form a mosaic conductive mesh structure. This structure can effectively prevent the aggregation and loss of scandium oxide particles, avoid the agglomeration problem of the hard carbon precursor material, and thus improve the rate performance of the hard carbon material. Compared with the traditional solid phase mixing, spray drying can also regulate the morphology structure of the hard carbon material to obtain a hard carbon material with a regular structure, a more uniform pore structure distribution, and a uniform pore size. At the same time, if micron-level scandium oxide is used in the spray drying process, the problem of uneven slurry mixing or agglomeration in the subsequent spray drying will occur due to its larger particle size and lower surface energy.
[0056] Preferably, the inlet air temperature of the spray drying is 120-300°C, for example, 120°C, 150°C, 175°C, 200°C, 225°C, 250°C, 275°C or 300°C.
[0057] Preferably, the outlet temperature of the spray drying is 100-200°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C.
[0058] Preferably, the rotation speed of the spray drying atomizer is 10000-30000 r / min, for example, 10000 r / min, 15000 r / min, 20000 r / min, 25000 r / min or 30000 r / min.
[0059] In the present invention, by adjusting the process parameters of spray drying, such as feed rate, atomizer rotation speed, drying temperature, etc., a hard carbon material with a more uniform pore structure can be obtained.
[0060] Preferably, the pressure applied during the compaction molding process is 5 to 10 MPa, for example, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa or 10 MPa.
[0061] Preferably, the carbonization method includes microwave sintering carbonization.
[0062] In the present invention, carbonization treatment is performed by a microwave sintering carbonization method to obtain a hard carbon negative electrode material with more uniform grains and higher density.
[0063] Specifically, the surface of the compacted material is first activated by an inert atmosphere, and then the dielectric loss in the microwave electromagnetic field is used to make the material absorb microwave energy, which is then converted into kinetic energy and potential energy of the molecules inside the material, so that the whole is heated to the sintering temperature to achieve the densification of the material. Compared with traditional atmosphere furnace sintering, microwave sintering can make the material evenly heated after absorbing microwaves, with a small internal temperature gradient, and can achieve low-temperature rapid sintering, and no additional heat source is required, which is highly efficient and energy-saving.
[0064] Preferably, the carbonization temperature is 1200-1650°C, for example, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C or 1650°C.
[0065] Preferably, the carbonization time is 10 to 30 min, for example, 10 min, 15 min, 20 min, 25 min or 30 min.
[0066] It is understandable that the specific atmosphere of carbonization in the present invention is no different from that of a conventional carbonization process, and can be carried out under a protective atmosphere, such as a nitrogen atmosphere and / or an inert gas atmosphere.
[0067] It should also be noted that, in the microwave sintering and carbonization process of the present invention, the specific microwave sintering parameters can be adaptively selected and adjusted by those skilled in the art according to the difference of the microwave instruments used.
[0068] For example, the power of the microwave sintering carbonization can be 1-10 kW, such as 1 kW, 2 kW, 3 kW, 4 kW, 5 kW, 6 kW, 7 kW, 8 kW, 9 kW or 10 kW.
[0069] In a third aspect, the present invention further provides a battery, comprising the hard carbon negative electrode material as described in the first aspect or the hard carbon negative electrode material prepared by the preparation method as described in the second aspect.
[0070] Preferably, the battery comprises a sodium ion battery.
[0071] The hard carbon negative electrode material provided by the present invention has high compaction density and excellent electrochemical performance. When it is used in a sodium ion battery, the first efficiency and rate performance of the sodium ion battery are significantly improved.
[0072] However, it is understandable that the hard carbon negative electrode material in the present invention can be used in not only sodium ion batteries but also lithium ion batteries. Those skilled in the art can make adaptive selections and adjustments based on actual needs.
[0073] For simplicity, the present invention only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the endpoints of the range is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.
[0074] Compared with the prior art, the present invention has the following beneficial effects:
[0075] (1) The hard carbon negative electrode material provided by the present invention has highly conductive nano-scandium oxide that can promote the selective adsorption of ester groups and carbonyl groups in sodium ion electrolytes, thereby inhibiting the occurrence of side reactions between hard carbon and electrolytes, reducing the formation of SEI films, and allowing more sodium ions to participate in the reversible embedding and extraction process, thereby improving the initial efficiency of hard carbon; nano-scandium oxide is also fixed in the pore structure of the hard carbon matrix material as a support to form an inlaid conductive network structure, which can effectively prevent the aggregation and loss of scandium oxide particles, making the hard carbon particles evenly distributed, so that even at high rate charge and discharge, electrons can be quickly transmitted in the electrode material; at the same time, the high specific surface area of nano-scandium oxide makes It can have more contact points with the hard carbon particles and generate van der Waals force, which helps to pull the hard carbon particles towards each other during the pressing process, making them more tightly combined together, thereby improving the compaction density of the material. Furthermore, nanoparticles have a larger specific surface area and more surface atoms. These surface atoms have higher chemical activity and thus become potential active sites. These active sites will chemically react with the functional groups on the hard carbon surface (such as carboxyl, hydroxyl, etc.) to form chemical bonds, and the chemical bonding effect can enhance the connection strength between the hard carbon particles, making it less likely for the hard carbon particles to undergo relative displacement during the compaction process, thereby being able to withstand higher pressures and achieve higher compaction densities.
[0076] (2) In the preparation method provided by the present invention, under the action of a binder, nano-scandium oxide and a hard carbon precursor material are uniformly mixed, and after a subsequent compaction molding process, the compaction density of the material is effectively improved. After a subsequent carbonization process, the nano-scandium oxide is fixed in the pore structure of the hard carbon matrix material as a support, and has excellent compaction density and electrochemical properties. The preparation method is simple to operate, does not require a complicated processing process, and is suitable for commercial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1 This is a SEM image of the hard carbon negative electrode material provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0078] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0079] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0080] Example 1
[0081] This embodiment provides a hard carbon negative electrode material, the hard carbon negative electrode material comprises a resin-based hard carbon matrix material, the resin-based hard carbon matrix material has a pore structure, and nano scandium oxide is fixed in the pore structure;
[0082] The median particle size of the nano scandium oxide is 100 nm, and the surface of the nano scandium oxide is modified with oxygen bridge bonds; the porosity of the resin-based hard carbon material is 40%; and the median particle size D50 of the hard carbon negative electrode material is 5 μm.
[0083] The preparation method of the hard carbon negative electrode material is as follows:
[0084] (1) adding a precipitant sodium oxalate solution with a concentration of 3 mol / L to a scandium sulfate solution with a scandium ion concentration of 2 mol / L and subjecting it to ultrasonic treatment to fully disperse it, and then quickly adding a soluble surfactant glycerol solution with a concentration of 1 mol / L to the above suspension, wherein the molar ratio of scandium sulfate, sodium oxalate and glycerol is 1:2:1, and performing a coprecipitation reaction. During the coprecipitation reaction, the pH value is 8.3-8.5. The reaction solution after the coprecipitation reaction is perfused with liquid nitrogen for rapid freezing and placed in a freeze dryer for freeze drying for 20 hours, and finally ground and sintered at 650° C. to obtain nano scandium oxide with a median particle size of 100 nm;
[0085] (2) mixing nano scandium oxide, phenolic resin and polyvinyl alcohol (concentration of 5 mol / L) into a slurry, wherein the amount of nano scandium oxide added is 2.5% of the mass of the phenolic resin, and the amount of polyvinyl alcohol added is 8% of the mass of the phenolic resin, and spray drying is performed. The spray drying parameters are: inlet air temperature of 200° C., outlet air temperature of 150° C., and the speed of the atomizer is 20,000 r / min;
[0086] The particles obtained by spray drying are compacted in a mold at a pressure of 10 MPa; then placed in a graphite sagger and subjected to high-temperature carbonization by microwave sintering at 1400° C. for 20 minutes in a nitrogen atmosphere, with a microwave power of 5 kW; after cooling, they are crushed and sieved to obtain the hard carbon negative electrode material.
[0087] Figure 1 The SEM image of the hard carbon negative electrode material provided in Example 1 of the present invention is shown.
[0088] Example 2
[0089] This embodiment provides a hard carbon negative electrode material, the hard carbon negative electrode material comprises a resin-based hard carbon matrix material, the resin-based hard carbon matrix material has a pore structure, and nano scandium oxide is fixed in the pore structure;
[0090] The median particle size of the nano scandium oxide is 5 nm, and the surface of the nano scandium oxide is modified with oxygen bridge bonds; the porosity of the resin-based hard carbon material is 30%; and the D50 of the hard carbon negative electrode material is 5 μm.
[0091] The preparation method of the hard carbon negative electrode material is as follows:
[0092] (1) adding a precipitant sodium oxalate solution with a concentration of 1 mol / L to a scandium sulfate solution with a scandium ion concentration of 0.5 mol / L and subjecting it to ultrasonic treatment to fully disperse it, and then quickly adding a soluble surfactant glycerol solution with a concentration of 0.1 mol / L to the above suspension, wherein the molar ratio of scandium sulfate, sodium oxalate and glycerol is 1:1:0.5, and performing a coprecipitation reaction. During the coprecipitation reaction, the pH value is 8.8-9. The reaction solution after the coprecipitation reaction is perfused with liquid nitrogen for rapid freezing and placed in a freeze dryer for freeze drying for 6 hours, and finally ground and sintered at 450° C. to obtain nano scandium oxide with a median particle size of 5 nm;
[0093] (2) mixing nano scandium oxide, phenolic resin and polymethyl methacrylate (concentration of 1 mol / L) into a slurry, wherein the amount of nano scandium oxide added is 0.5% of the mass of the phenolic resin, and the amount of polyvinyl alcohol added is 5% of the mass of the phenolic resin, and spray drying is performed. The spray drying parameters are: inlet air temperature of 120° C., outlet air temperature of 100° C., and the speed of the atomizer is 10000 r / min;
[0094] The particles obtained by spray drying are compacted in a mold at a pressure of 10 MPa; then placed in a graphite sagger and subjected to high-temperature carbonization by microwave sintering at 1650° C. for 10 minutes in a nitrogen atmosphere, with a microwave power of 10 kW; after cooling, they are crushed and sieved to obtain the hard carbon negative electrode material.
[0095] Example 3
[0096] This embodiment provides a hard carbon negative electrode material, the hard carbon negative electrode material comprises a resin-based hard carbon matrix material, the resin-based hard carbon matrix material has a pore structure, and nano scandium oxide is fixed in the pore structure;
[0097] The median particle size of the nano scandium oxide is 250nm, and the surface of the nano scandium oxide is modified with oxygen bridge bonds; the porosity of the resin-based hard carbon material is 50%; and the D50 of the hard carbon negative electrode material is 10μm.
[0098] The preparation method of the hard carbon negative electrode material is as follows:
[0099] (1) adding a precipitant sodium oxalate solution with a concentration of 3 mol / L to a scandium sulfate solution with a scandium ion concentration of 2 mol / L and subjecting it to ultrasonic treatment to fully disperse it, and then quickly adding a soluble surfactant glycerol solution with a concentration of 1 mol / L to the above suspension, wherein the molar ratio of scandium sulfate, sodium oxalate and glycerol is 1:5:1.5, and performing a coprecipitation reaction. During the coprecipitation reaction, the pH value is 9.5-9.8. The reaction solution after the coprecipitation reaction is perfused with liquid nitrogen for rapid freezing and placed in a freeze dryer for freeze drying for 35 hours, and finally ground and sintered at 850° C. to obtain nano scandium oxide with a median particle size of 250 nm;
[0100] (2) mixing nano scandium oxide, phenolic resin and polymethyl methacrylate (concentration of 5 mol / L) into a slurry, wherein the amount of nano scandium oxide added is 5% of the mass of the phenolic resin, and the amount of polyvinyl alcohol added is 10% of the mass of the phenolic resin, and spray drying is performed. The spray drying parameters are: inlet air temperature of 300° C., outlet air temperature of 200° C., and the speed of the atomizer is 30,000 r / min;
[0101] The particles obtained by spray drying are compacted in a mold at a pressure of 5 MPa; then placed in a graphite sagger and subjected to high-temperature carbonization by microwave sintering at 1200° C. for 30 minutes under a nitrogen atmosphere, with a microwave power of 10 kW; after cooling, they are crushed and sieved to obtain the hard carbon negative electrode material.
[0102] Example 4
[0103] The difference between this embodiment and embodiment 1 is that the hard carbon precursor material in this embodiment is coconut shell.
[0104] The rest of the preparation methods and parameters were the same as those in Example 1.
[0105] Example 5
[0106] The difference between this embodiment and embodiment 1 is that the D50 of the nano scandium oxide in this embodiment is 300 nm.
[0107] In the preparation method, the molar ratio of the scandium salt, the precipitant and the surfactant is adjusted to be 1:5:0.5.
[0108] The rest of the preparation methods and parameters were the same as those in Example 1.
[0109] Example 6
[0110] The difference between this embodiment and embodiment 1 is that the amount of nano scandium oxide added in this embodiment is 0.1% of the mass of the phenolic resin.
[0111] The rest of the preparation methods and parameters were the same as those in Example 1.
[0112] Example 7
[0113] The difference between this embodiment and embodiment 1 is that the amount of nano scandium oxide added in this embodiment is 6% of the mass of the phenolic resin.
[0114] The rest of the preparation methods and parameters were the same as those in Example 1.
[0115] Example 8
[0116] The difference between this embodiment and embodiment 1 is that the amount of polyvinyl alcohol added in this embodiment is 3% of the mass of the phenolic resin.
[0117] The rest of the preparation methods and parameters were the same as those in Example 1.
[0118] Example 9
[0119] The difference between this embodiment and embodiment 1 is that the amount of polyvinyl alcohol added in this embodiment is 12% of the mass of the phenolic resin.
[0120] The rest of the preparation methods and parameters were the same as those in Example 1.
[0121] Example 10
[0122] The difference between this embodiment and embodiment 1 is that in this embodiment, the slurry mixed in step (2) is not spray-dried but directly placed in a drying box for drying.
[0123] The rest of the preparation methods and parameters were the same as those in Example 1.
[0124] Comparative Example 1
[0125] The difference between this comparative example and Example 1 is that the hard carbon negative electrode material provided in this comparative example does not contain nano scandium oxide.
[0126] In the preparation method, step (1) is not performed.
[0127] The rest of the preparation methods and parameters were the same as those in Example 1.
[0128] Comparative Example 2
[0129] The difference between this comparative example and Example 1 is that the scandium oxide in this comparative example is a commercially available product with a median particle size of 1.3 μm.
[0130] In the preparation method, nano-scale scandium oxide is directly replaced by micron-scale scandium oxide.
[0131] The rest of the preparation methods and parameters were the same as those in Example 1.
[0132] Comparative Example 3
[0133] The difference between this comparative example and Example 1 is that the preparation method of this comparative example does not contain the binder polyvinyl alcohol.
[0134] The rest of the preparation methods and parameters were the same as those in Example 1.
[0135] Comparative Example 4
[0136] The difference between this comparative example and Example 1 is that in this comparative example, the particles after spray drying are carbonized, and no compaction and molding process is performed.
[0137] The rest of the preparation methods and parameters were the same as those in Example 1.
[0138] The hard carbon negative electrode materials provided in Examples 1-10 and Comparative Examples 1-4 were tested for compaction density. The test conditions were: a compaction powder resistance meter was used to test the compaction density of the hard carbon negative electrode materials. The test range was 50-200 MPa. The mass of the material used in the test was 0.5 g. The test results are shown in Table 1.
[0139] Table 1
[0140]
[0141]
[0142] [Preparation and performance testing of sodium ion batteries]
[0143] Sodium ion battery preparation:
[0144] The hard carbon negative electrode material, conductive agent Super P and polyvinylidene fluoride provided in the embodiment and the comparative example were respectively prepared into a slurry with N-methylpyrrolidone (NMP) in a ratio of 8:1:1, stirred for 24 hours, coated on a carbon-coated copper foil, and dried in an oven at 80°C for 24 hours. The dried electrode was cut into 12 mm discs with a loading of 1.24 mg / cm 2 , and a hard carbon negative electrode is obtained.
[0145] Sodium foil was used as the counter electrode, glass fiber (GF / A) was used as the separator, and 1 mol / L NaFP6 was dissolved in a mixed solvent of EC and DMC as the electrolyte, in which the volume ratio of EC to DMC was 1:1.
[0146] The hard carbon negative electrode, separator and sodium foil were stacked, injected with electrolyte, and assembled into a 2032 model button battery in a glove box.
[0147] Performance Test:
[0148] (a) First efficiency: The test was conducted using a blue electric test cabinet at 25°C, with a current density of 30 mA / g, a nominal specific capacity of 300 mAh / g, a charge cut-off voltage of 2.0 V, and a discharge cut-off voltage of 0 V. The first coulombic efficiency (first efficiency) can be calculated by the ratio of the first charge specific capacity to the first discharge specific capacity. The specific formula is: first efficiency = first charge specific capacity / first discharge specific capacity × 100%.
[0149] (b) Rate performance: The rate charge and discharge method adopted is to charge and discharge in sequence at 5 different current densities, namely 30mA / g, 60mA / g, 100mA / g, 300mA / g, and 600mA / g. Five cycles of charge and discharge are performed at each current density. After the end, long cycle charge and discharge are performed at a current density of 30mA / g to test the capacity of the battery in the large rate charge and discharge test. The capacity at 600mA / g is used as the test result of this test.
[0150] The test results of the above tests are shown in Table 2.
[0151] Table 2
[0152]
[0153]
[0154] In summary, in the present invention, nano scandium oxide is fixed in the pore structure of the hard carbon matrix material as a support, which on the one hand improves the compaction density of the hard carbon negative electrode material, and on the other hand forms an embedded conductive network structure, thereby improving the electrochemical performance of the hard carbon negative electrode material.
[0155] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A hard carbon negative electrode material, characterized in that: The hard carbon negative electrode material comprises a hard carbon matrix material having a pore structure, in which nano scandium oxide is fixed.
2. The hard carbon negative electrode material according to claim 1, characterized in that: The surface of the nano scandium oxide is modified with oxygen bridge bonds; Preferably, the median particle size D50 of the nano scandium oxide is 5 to 250 nm.
3. The hard carbon negative electrode material according to claim 1 or 2, characterized in that: The hard carbon matrix material includes a resin-based hard carbon matrix material; Preferably, the porosity of the hard carbon matrix material is 20% to 55%; Preferably, the median particle size D50 of the hard carbon negative electrode material is 5 to 10 μm.
4. A method for preparing a hard carbon negative electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: The hard carbon negative electrode material is obtained by mixing nano scandium oxide, a hard carbon precursor material and a binder solution, compacting and molding, and carbonizing.
5. The preparation method according to claim 4, characterized in that: The preparation method of the nano scandium oxide comprises: Mixing and dispersing a scandium salt solution and a precipitant solution, performing a coprecipitation reaction, and sintering to obtain nano scandium oxide; Preferably, the mixing and dispersing process further includes a surfactant solution; Preferably, the surfactant comprises any one of glycerol, polyethylene glycol, Span or Tween, or a combination of at least two thereof; Preferably, the molar ratio of the scandium salt, the precipitant and the surfactant is 1:(1-5):(0.5-1.5); Preferably, the concentration of the scandium salt solution is 0.5 to 3.5 mol / L; Preferably, the concentration of the precipitant solution is 1 to 6 mol / L; Preferably, the concentration of the surfactant solution is 0.1 to 1.5 mol / L; Preferably, the pH value of the coprecipitation reaction is 8 to 10; Preferably, the reaction solution after the coprecipitation reaction is freeze-dried; Preferably, the freeze-drying time is 6 to 36 hours; Preferably, the sintering temperature is 450-850° C., and the sintering time is 0.5-2 h.
6. The preparation method according to claim 4 or 5, characterized in that: The amount of the nano scandium oxide added is 0.5% to 5% of the mass of the hard carbon precursor material; Preferably, the amount of the binder added is 5% to 10% of the mass of the hard carbon precursor material; Preferably, the hard carbon precursor material comprises a resin; Preferably, the binder comprises any one of paraffin, polyvinyl alcohol, polymethyl methacrylate or polyurethane, or a combination of at least two thereof; Preferably, the concentration of the binder solution is 1-10 mol / L.
7. The preparation method according to claim 4, characterized in that: The mixed solution is spray-dried and then compacted and molded; Preferably, the air inlet temperature of the spray drying is 120-300° C., the air outlet temperature of the spray drying is 100-200° C., and the rotation speed of the atomizer of the spray drying is 10000-30000 r / min.
8. The preparation method according to claim 4, characterized in that: The carbonization method includes microwave sintering carbonization; Preferably, the carbonization temperature is 1200-1650° C., and the carbonization time is 10-30 min.
9. A battery, characterized in that: The battery comprises the hard carbon negative electrode material according to any one of claims 1 to 3 or the hard carbon negative electrode material prepared by the preparation method according to any one of claims 4 to 8.
10. The battery according to claim 9, characterized in that The battery comprises a sodium ion battery.
Citation Information
Patent Citations
Lithium ion battery negative electrode material, preparation method thereof and application of material
CN109301219A
Scandium-containing sodium ion battery negative electrode material as well as preparation method and application thereof
CN117374208A
Lithium ion secondary battery
JP2011076822A
Dry anode film, and dry anode and lithium battery including the same
US20240322127A1